Intra and inter: Alterations in functional brain resting-state networks in patients with functional constipation - Zhang, Dan; Zhou, Zai-Long; Xing, Ting; Zhou, Mei-Yu; Wan, Ye-Ming; Chang, Shu-Chen; Wang, Ya-Li; Qian, Hai-Hua (Frontiers in Neuroscience, 2022)
Background: Functional constipation (FCon), a symptom-based functional gastrointestinal disorder without an organic etiology, has been demonstrated to induce functional and structural brain alterations. However, the previous studies almost focused on the isolated brain regions which caused brain plasticity. Little is known about the altered large-scale interaction of brain networks related to FCon. Methods: In this study, 20 FCon patients and 20 healthy controls were recruited. We used group independent component analysis (GICA) to identify resting-state networks (RSNs). And the intra- and internetwork alterations in the RSNs of the FCon patients were investigated. Results: Fourteen independent RSNs were obtained. Differences in the intranetwork showed decreased activities in bilateral caudate of RSN 3 (strongly related to emotional and autonomic processes) and decreased activities in the left precuneus of RSN 10 (default mode network). Notably, the FCon patients exhibited significantly decreased interactive connectivity between RSNs, mostly involving the connections to the visual perception network (RSN 7-9). Conclusion: Findings indicated that brain plastic changes were extensive within and across related RSNs in the FCon patients compared with the healthy controls. And the macroscopic brain alterations in FCon were associated with interoceptive abilities, emotion processing, and sensorimotor control. These insights could therefore provide the important clues for new treatment strategies for FCon.